2018
DOI: 10.1039/c7nr08497h
|View full text |Cite
|
Sign up to set email alerts
|

Controlled doping of transition metal dichalcogenides by metal work function tuning in phthalocyanine compounds

Abstract: We explored surface charge transfer interaction between a family of phthalocyanine (Pc) compounds and transition metal dichalcogenides (TMDs). Comparing the device characteristics of TMD field-effect transistors (FETs), we demonstrate both p-type and n-type doping of TMDs by tuning the work function of the metal substitution in the Pc compound. Our findings suggest a near linear correlation between the metal work function and doping level. Such doping predictability has yet to be achieved whereas we provide he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 18 publications
0
41
0
Order By: Relevance
“…Reprinted with permission from reference [33].Copy-right2 014 American Chemical Society. [39] It was found that NaPc resulted in n-doping of the nanosheets in contrastt oF e, Pt and CuPc, for which p-doping was observed. The excesse lectrons favor the formation of trions insteado fe xcitons, thus the photoluminescence intensity prior of annealing was decreased and afterwards increased as a result of more effective charge recombination.…”
Section: Noncovalent Surfacef Unctionalization Of Mos 2 Nanosheets Wimentioning
confidence: 98%
See 2 more Smart Citations
“…Reprinted with permission from reference [33].Copy-right2 014 American Chemical Society. [39] It was found that NaPc resulted in n-doping of the nanosheets in contrastt oF e, Pt and CuPc, for which p-doping was observed. The excesse lectrons favor the formation of trions insteado fe xcitons, thus the photoluminescence intensity prior of annealing was decreased and afterwards increased as a result of more effective charge recombination.…”
Section: Noncovalent Surfacef Unctionalization Of Mos 2 Nanosheets Wimentioning
confidence: 98%
“…Moreover,since phthalocyanines can be customdesigned so as to carry electron-donating or -withdrawing groups,c opper-, iron-, platinum-, and sodium-chelated sulfonated phthalocyanines were deposited ontom echanicallye x-foliatedM oS 2 monolayers and the doping effects were probed. [39] It was found that NaPc resulted in n-doping of the nanosheets in contrastt oF e, Pt and CuPc, for which p-doping was observed. Further variation of the dye, by insertion of fluorine atoms( sulfonates were reserved) possessing electronwithdrawing characteristics, and chelation with copper,d emonstrated am ore intense p-doping effect relative to the nonfluorine CuPc.…”
Section: Noncovalent Surfacef Unctionalization Of Mos 2 Nanosheets Wimentioning
confidence: 98%
See 1 more Smart Citation
“…Such evidence can be attributed to the formation of p–n junctions, in agreement with previous studies. [ 9,11b ] By further coordinating the fPys, we have observed shifts in two opposite directions: for 3,5‐FP and 3‐FP, the I ds – V g curves shift to positive voltages while for 2‐FP and 4‐AP, the curves shift to the negative direction.…”
Section: Introductionmentioning
confidence: 97%
“…[ 8 ] Thus, they are appropriate candidates to functionalize ultra‐thin MoS 2 films, eventually via the formation of Van der Waals organic‐inorganic heterostructures. This type of heterostructures has been proved to feature charge transfer from the LUMO of MPc to the conduction band of MoS 2 , resulting in doping in field‐effect transistors (FETs), [ 9 ] Raman enhancement, [ 10 ] photoresponse improvement, [ 11 ] etc.…”
Section: Introductionmentioning
confidence: 99%